Defense against Shoulder Surfing Attack for Recognition Based Graphical Password (International Journal of Engineering and Computer Science, 2014)
Recognition based Graphical password is secure against shoulder surfing attack, guessing and capture attacks. In this paper we propose the technique for defense against shoulder surfing attack. This technique is based on grid of images, where the user first give his username and then identifies the password images eliminate that row and column dost not contain password image apply this process twice and then mapped the password into another blank grid.